Implementation IoT in System Monitoring Hydroponic Plant Water Circulation and Control - Nurhasan, Usman; Prasetyo, Arief; Lazuardi, Gilang; Rohadi, Erfan; Pradibta, Hendra (International Journal of Engineering and Technology, 2018)
Hydroponics is the cultivation of plants by utilizing water without using soil by emphasizing the fulfillment of nutritional needs for plants. Deep Flow Technic (DFT) is a type of hydroponics that implements a continuous flow of nutrients and there is a pool of half of the diameter of the pipe that inundates the roots of the plant. A common obstacle experienced by DFT is the lack of maintenance of plant growth elements such as water circulation, light intensity, temperature, humidity and pH of the water which causes these plants not to grow optimally. Then it is necessary to monitor and control the circulation of water on DFT-based IoT hydroponics to anticipate changes in plant growth elements. Data on plant growth elements are acquired by sensors integrated with Raspberry Pi. In the monitoring process using the website will display data on plant growth elements in the form of pH, temperature, humidity and water level in the hydroponic reservoir. Temperature and humidity are used as water circulation control parameters that are processed using the Fuzzy Sugeno Method. From the results of the tests that have been carried out, the system can monitor plant growth elements displayed on the website in real time and control water circulation automatically. The system applied in the hydroponics of mustard greens also produces significant growth in leaf number and plant height.Â Â Â